Materials for Sustainable Energy 2010
DOI: 10.1142/9789814317665_0048
|View full text |Cite
|
Sign up to set email alerts
|

Strongly enhanced current densities in superconducting coated conductors of YBa2Cu3O7−x + BaZrO3

Abstract: There are numerous potential applications for superconducting tapes, based on YBa 2 Cu 3 O 7-x (YBCO) films coated onto metallic substrates [1]. A long established goal of more than 15 years has been to understand the magnetic flux pinning mechanisms which allow films to maintain high current densities out to high magnetic fields [2]. In fact, films carry 1-2 orders of magnitude higher current densities than any other form of the material [3]. For this reason, the idea of further improving pinning has received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 18 publications
2
51
1
Order By: Relevance
“…Further improvement of the performance of these films can be expected when columnar-type defects are incorporated. Experiences accumulated over the past decades on creating self-assembled columnar defects in cuprates films 35 via chemical synthesis could help promote similar critical current enhancement in iron-based superconducting films. In this respect, SmFeAsO 1 À x F x -based superconducting products with performance comparable to the state-of-the-art of cuprates can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Further improvement of the performance of these films can be expected when columnar-type defects are incorporated. Experiences accumulated over the past decades on creating self-assembled columnar defects in cuprates films 35 via chemical synthesis could help promote similar critical current enhancement in iron-based superconducting films. In this respect, SmFeAsO 1 À x F x -based superconducting products with performance comparable to the state-of-the-art of cuprates can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Superconductive/ thermoelectric material performance can be improved by adding nanoparticles (NPs) that disrupt the order parameter/phonon density while leaving the matrix and electronic structure of the superconductor/thermoelectric intact. [1][2][3][4] In the case of thermoelectrics, the reduction of lattice thermal conductivity through phonon scattering by size-controlled NPs has been predicted in the seminal paper by Hicks and Dresselhaus. 5 This approach has already been demonstrated to be effective in metallic materials, such as Bi 2 Te 3 /Sb 2 Te 3 multilayers 6 and PbTe bulk material 1 with natural NP additions with a significant enhancement of the figure of merit (ZT) that has reached up to~2 at 800 K. In comparison with metallic materials, oxides offer the advantages of reduced cost, nontoxicity and higher stability at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…After the seminal works demonstrated that second-phase additions 4,12 to RE-Ba-Cu-O (rare earth (RE)) (REBCO) thin films grown using pulsed laser deposition (PLD) significantly improved the current carrying performance in an applied magnetic field, 3,[13][14][15] it was shown that the morphology of the inclusions depends on the synthesis 1 Materials Physics and Applications Division, Los Alamos National Laboratory, Los Alamos, NM, USA; 2 Graduate School of Science and Technology, Seikei University, Tokyo, Japan; 3 Nanostructures Research Laboratory, Japan Fine Ceramics Center, Nagoya, Japan; 4 National Institute of Advanced Industrial Science and Technology, Ibaraki, Japan; method (that is, in situ vs ex situ). 3,16 Moreover, recent work has shown that large quantities (⩾10%) of second-phase additions are required to obtain the desired level of performance in superconductors.…”
Section: Introductionmentioning
confidence: 99%
“…This approach resulted in pancake-like 211 particles with an average size of 15 nm distributed in the YBCO film, which produced some enhancement in pinning along c and much higher improvements for H//a,b. Correlated pinning along the c-axis was also observed when seemingly randomly distributed 10-nm-wide BaZrO 3 (BZO) particles were inserted in the YBCO film by ablating from a PLD target synthesized using Ba excess and added Zr [41]. In the last study the observed correlated pinning along the c-axis was related to misfit dislocations between the nanoparticles and the superconducting matrix, which aligned along the c direction, with an areal density of 400 µm -2 compared to 80 µm -2 for undoped YBCO films.…”
Section: Artificial Introduction Of Flux Pinning Nanostructuresmentioning
confidence: 99%